Recalibration of partial environmental load factors for sustainable design of offshore structures in Malaysia - Sambu Potty, Narayanan (2012)
In the face of increased awareness of the human impact on the global changes, such as the frequent occurrence of natural disasters, has led the professionals to seek new methods of designing structures that not only can fulfill the desired requirements but also are sustainable in the long term. This paper presents and discusses the adoption of sustainable design in offshore industry, most particularly in Malaysia. Reliability analysis is applied to evaluate the reliability indices, and subsequently determine the partial environmental load factors of tubular members and joints of a fixed steel jacket platform. The partial load factor is determined such that it reflects the local environmental load conditions.